Early Detection of Congenital Heart Disease in Pregnant Young Women at Risk - Putri, Valerinna Yogibuana Swastika (Heart Science Journal, 2022)
Cardiovascular disease (CVD) is one of the non-communicable diseases in which the leading cause of death worldwide at 48%1. CVD contains a spectrum of diseases, one of which is Congenital Heart Defect (CHD). CHD is one of the contributors to morbidity from young until adulthood. The advancement of surgical correction and medical therapy made it possible for early structural correction, as uncorrected CHD while patients were still young posed a risk of health outcome deterioration later in life. CHD affected especially pregnant individuals. A pregnant woman diagnosed with CHD would often complain of significantly significant deterioration of health condition and quality of life as they have a higher susceptibility to cardiovascular complications than women in general. Pregnant women diagnosed with CHD in developing countries more often presented with signs indicating complications of CHD, such as Eisenmenger syndrome, signs of heart failure, Pulmonary Hypertension (PH), cyanosis, and NYHA functional classes II and III, which indicate later diagnosis and treatment further into adulthood in these patients. Lack of expertise and facility for diagnosis of CHD posed a major challenge in reducing mortality related to CHD in these countries. Therefore the need for a screening method at least for directing further referral to major health centers is still in high demand.